2004
DOI: 10.1177/030981680408400119
|View full text |Cite
|
Sign up to set email alerts
|

Culture that works? Creative industries development in a working-class city

Abstract: Creative industries development has been underway in the city of Stoke-on-Trent for the past fifteen years. Two urban quarters, a creative industries network, 'design-led' regeneration initiatives, and live-work spaces for craft businesses are some of the main projects undertaken in this period. In the past year, this raft of developments has been augmented by a creative industries mapping exercise, and a subsequent funding bid that seeks to draw on UK government and European structural funds in order to act o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 5 publications
1
44
0
1
Order By: Relevance
“…On the whole, research that explores the local identity of the Potteries has focused on pottery (and mining) exploring the public realm of work (Hart 2005;Popp 2003;Sarsby 1988) and the 'official' museum culture which also primarily focuses on art history and production. However, the experiences of pottery workers, their communities built around the pot banks, the decline of mining and pottery production locally, the urban and heritage legacy (Jayne 2000a(Jayne , 2000b) that developed alongside are all important parts of the local history and provide much basis for local pride, as can be seen in many studies of local knowledge, leisure, and museum visiting (DeBres 1991;Waterton 2011;Williams 2006). …”
Section: What Is Turning Over?mentioning
confidence: 99%
See 2 more Smart Citations
“…On the whole, research that explores the local identity of the Potteries has focused on pottery (and mining) exploring the public realm of work (Hart 2005;Popp 2003;Sarsby 1988) and the 'official' museum culture which also primarily focuses on art history and production. However, the experiences of pottery workers, their communities built around the pot banks, the decline of mining and pottery production locally, the urban and heritage legacy (Jayne 2000a(Jayne , 2000b) that developed alongside are all important parts of the local history and provide much basis for local pride, as can be seen in many studies of local knowledge, leisure, and museum visiting (DeBres 1991;Waterton 2011;Williams 2006). …”
Section: What Is Turning Over?mentioning
confidence: 99%
“…Often Stoke-on-Trent is considered in the shadow of the cultural and economic regenerations practiced more successfully (Jayne 2004) in Manchester and Birmingham:…”
Section: What Is Turning Over?mentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson (1993) has suggested that the heritage of the pottery industry is reflected in local interest in craftwork skills. However, some have suggested that the shadow of the pottery industry has hampered efforts at regeneration, a situation exacerbated by the geographical make-up of the city as a conurbation of small towns (Jayne, 2004).…”
Section: Archaeology Objects and Identitymentioning
confidence: 99%
“…'soft' location factors in terms of debate on the competitiveness of regions (Bontje & Musterd, 2009). The Zlín Region is selected for the analysis, with respect to traditional creative industries of the local economy, i.e., film production, design, and glass industry (see e.g., Bell & Jayne, 2003;Jayne, 2004).…”
Section: Introductionmentioning
confidence: 99%